(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Several problems in the teaching and learning process at SD Negeri Ganting, Gedangan District, Sidoarjo Regency, including low interest and motivation in learning for students which leads to low learning achievement, are the driving factors for this research. The use of technology in education is increasingly developing in the current digitalization era, quizzes and educational games are starting to be integrated as learning resources. The purpose of this study was to determine the effect of learning tactics such as educational games and quizzes on the learning interests of elementary school students. The findings of this study show the impact of educational games and quizzes as learning tools to motivate elementary school students to learn. This is indicated by the learning achievement of students who use educational games and quizzes together with other media. Students’ willingness to learn increases and education becomes more effective and efficient when learning techniques involving quizzes and educational games are used.